Balance Sheet of a Central Bank – A Source of Information about the Economic Position of a Country. A Comparative Study of USA and China - Rumiana GÓRSKA (Revista de Management Comparat International)
The objective of the paper is to present the results of a comparative analysis of the balance sheets of the central banks of USA and China in order to investigate how they reflect the changes in the international positions of these countries on the world economic scene after 2000. The growth of a country’s GDP is usually accompanied by an increase in the monetary base (and consequently the monetary aggregates), but there are also other factors determining the changes in a central bank’s balance sheet. The study presented in the paper contains two steps. First, the collateral of money issue in USA and China during the period 2000-2012 is compared. The main collateral of money issue in USA are U.S. Treasury securities, but after 2008 also mortgage-backed securities. The main collateral of money issue in China are foreign assets. Second step of the study is a comparison of the international position of these countries. The presented analysis confirms that the collateral of money issue in USA is debt, which reflects the position of USA as a world debtor. The collateral of money issue in China are foreign assets, mainly foreign currencies, which reflects the role of China as a world exporter and creditor.